Effects of intraperitoneally administered ubiquinone on the level of total lipid and fatty acids in rat liver - Celik, Sait; Akarcay, Hatice; Yilmaz, Okkes; Ozkaya, Ahmet (Wiley, 2006)
The purpose of the present study was to evaluate the effect of ubiquinone (coenzyme Q-10) on total lipid and fatty acid composition of liver tissues in rats. Twenty male wistar rats were randomly divided into two groups. The first group was used as a control. The second group received ubiquinone (8 mg/every other day) intraperitoneally. This administration was done for a period of 38 days. Body weight increases in animals fed diets for 38 days were on average 35 gin control group (C), and only 11 g in the ubiquinone group. Total lipid content of liver tissues in the ubiquinone group (UB) decreased significantly (p < 0.0001) compared to the control group (C). The ratio of 22:6 and total w3 fatty acid in the UB increased (p < 0.01) compared to C. While the level of oleic acid (18:1), palmitoleic acid (16:1) and total monounsaturated fatty acid (MUFA) in UB significantly decreased (p < 0.01, p < 0.001, p < 0.001 respectively), the level of stearic acid (18:0) in liver tissue increased (p < 0.05) in the same group when compared to C. Stearoyl-CoA desaturase (SCD) is the rate-limiting enzyme catalyzing the synthesis of monounsaturated fatty acid mainly oleate (18:1). We speculate that ubiquinone inhibits SCD activity. SCD is an important metabolic control point in body weight regulation. Our results indicate that ubiquinone supplementation may have an inhibitory effect on obesity and it seems that the level of 22:6 in liver increased due to ubiquinone. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: ubiquinone; obesity; total lipid; fatty acid